2017
DOI: 10.1364/boe.8.001607
|View full text |Cite
|
Sign up to set email alerts
|

Review of intraoperative optical coherence tomography: technology and applications [Invited]

Abstract: During microsurgery, en face imaging of the surgical field through the operating microscope limits the surgeon's depth perception and visualization of instruments and subsurface anatomy. Surgical procedures outside microsurgery, such as breast tumor resections, may also benefit from visualization of the sub-surface tissue structures. The widespread clinical adoption of optical coherence tomography (OCT) in ophthalmology and its growing prominence in other fields, such as cancer imaging, has motivated the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 193 publications
(323 reference statements)
0
89
0
2
Order By: Relevance
“…Large cyst occupying more than half of anterior chamber, cyst required extensive surgical manipulation during surgery and in cases of incomplete removal, chances of recurrence will be there 14 15. iOCT is being used for various anterior and posterior segment surgery like Descemet’s stripping automated endothelial keratoplasty, deep anterior lamellar keratoplasty, inner limiting membrane peeling during various retinal surgery and others 16. In this case, we separated the anterior cyst wall from the endothelium by viscodissection under the guidance of iOCT, which revealed the definite separation of the cyst wall from the endothelium.…”
Section: Discussionmentioning
confidence: 87%
“…Large cyst occupying more than half of anterior chamber, cyst required extensive surgical manipulation during surgery and in cases of incomplete removal, chances of recurrence will be there 14 15. iOCT is being used for various anterior and posterior segment surgery like Descemet’s stripping automated endothelial keratoplasty, deep anterior lamellar keratoplasty, inner limiting membrane peeling during various retinal surgery and others 16. In this case, we separated the anterior cyst wall from the endothelium by viscodissection under the guidance of iOCT, which revealed the definite separation of the cyst wall from the endothelium.…”
Section: Discussionmentioning
confidence: 87%
“…High‐frequency ultrasound biometry provides real‐time, high‐resolution images but requires a contact medium between the probe and the eye to reduce signal reflection. In contrast, OCT provides a noncontact, real‐time, high‐resolution imaging modality that can be integrated into surgical instruments and microscopes . Most importantly, it has been shown that intraocular tissues can be visualized in OCT scans in both anterior and posterior segments …”
Section: Background and Motivationmentioning
confidence: 99%
“…Although CT and MRI both provide quantitative prediction with computer‐aided diagnosis based on morphological features, usually the resolution is on the order of millimeters and is low . Because of the raised volumetric real‐time imaging performance, the ultra‐high resolution and intra‐surgical OCT (optical coherence tomography) have been developed as a computer‐aided diagnosis tool in detecting the boundary of benign or cancerous desease .…”
Section: Introductionmentioning
confidence: 99%